Prediction of Self-efficacy and Self-care Behaviors among Diabetic Women Based on their Attitude towards Gestational Diabetes - Masoumeh Kordi; Mahsima Banaei Heravan (Mashhad University of Medical Sciences, 2020)
Background and Aims: Gestational diabetes mellitus (GDM) is the most commonly observed metabolic disorder in pregnancy. Self-care and self-efficacy are recognized as contributing factors to the control of this disease. Nonetheless, these factors might be affected by such issues as one's knowledge and attitude. The present study aimed to assess how attitude towards GDM could predict diabetic women's self-care and self-efficacy during pregnancy. Materials and Methods: This predictive correlational study was conducted on 400 women with GDM referring to health centers and maternity clinics in Mashhad, Iran. Data were collected using a demographic and midwifery questionnaire, a diabetes attitude scale, a self-efficacy questionnaire, and a self-care questionnaire retrieved from the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire. The data were analyzed in SPSS software (version22) using Spearman and Pearson correlation coefficients, as well as multiple liner regression and general linear regression models. Results: A direct linear relationship was observed between the attitude and self-efficacy (p <0/0001; r=0/23). However, no significant relationship was found between attitude and self-care (P=0.365; r=0.45). Based on the results of the general linear regression model, attitude could predict self-efficacy (p <0.0001; F=27.798; β=0.334). There was also a significant direct relationship between self-efficacy and self-care. Conclusion: It can be concluded that midwives could tailor interventions to improve the attitude of women towards GDM to enhance their sense of self-efficacy in order to execute diabetes self-care activities to manage their disease, effectively.